Analysis of Compliance with DM Management During the Covid-19 Period at the Solok City Health Center - Tintin Sumarni; Yulastri; Novi Herawati (POLTEKKES KEMENKES PADANG, 2023)
Based on the 2018 Basic Health Research (RISKESDAS), one of the PTM whose prevalence has increased significantly is diabetes mellitus reaching 8.5%. prevalence in West Sumatra was 13,834, while the City of Solok was 1,796 in 2018. Diabetes mellitus can increase the risk of death in Covid-19 patients. The purpose of this study was to determine the compliance of Type-II DM patients in the management of the five pillars of DM (diet, taking medication, physical activity, education, and blood sugar control. This study used a descriptive-analytic cross sectional approach. The population was type 2 DM patients who visited the posbindu). The last 3 months amounted to 65 people.The results showed that adherence to medication, diet, education, and blood sugar control had a significant relationship with blood sugar levels with p value = <0.05. it turns out that the most dominant relationship with blood sugar levels is the regularity of taking medication with (p value 0.002) OR = 72.500. It is hoped that people who suffer from diabetes mellitus can understand the importance of implementing DM management. There is a policy from the Health Office involving family members to care so that the five pillars of DM management can be implemented properly so that DM patients can lead a life without complications.